2009
DOI: 10.1007/s10067-009-1312-y
|View full text |Cite
|
Sign up to set email alerts
|

Foot pain in rheumatoid arthritis prevalence, risk factors and management: an epidemiological study

Abstract: Foot involvement is a major feature of rheumatoid arthritis (RA). Most epidemiological studies of the RA foot report radiological changes and results of clinical examination. This study aimed to determine the prevalence of foot symptoms, frequency of foot assessment and access to foot care from the perspective of people with RA. A questionnaire was sent to 1,040 people with RA throughout the UK enquiring about foot symptoms, their anatomical distribution (via validated mannequins) availability of podiatry serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
3
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 26 publications
12
164
3
1
Order By: Relevance
“…The women with an increased fear of falling demonstrated greater foot impairment, disability and more comorbid conditions. The differences in foot-related impairment and disability between cases and controls may have been attributed to factors that include lower limb muscle weakness [26], joint stiffness [25] or postural instability [23]. However, foot pain was not significantly different between the cases and controls.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The women with an increased fear of falling demonstrated greater foot impairment, disability and more comorbid conditions. The differences in foot-related impairment and disability between cases and controls may have been attributed to factors that include lower limb muscle weakness [26], joint stiffness [25] or postural instability [23]. However, foot pain was not significantly different between the cases and controls.…”
Section: Discussionmentioning
confidence: 92%
“…We found no correlation found between fear of falling and foot pain. Foot pain is the most common problem facing people with RA both generally and specifically related to their feet [25]. However, all participants in the study were part of an ongoing foot care programme where they received regular general podiatric care that included the reduction of foot pain with the use of non-surgical interventions that included foot orthoses and footwear advice.…”
Section: Discussionmentioning
confidence: 99%
“…Foot complaints are frequently seen in people with RA [3,4], and the extent of these pathologies contributes to the overall disability experienced [5]. Involvement of the foot in RA has been shown to be an important marker for impaired mobility and reduced functional capacity; this subsequent loss of mobility due to foot pathology can have a profoundly negative impact on social interaction [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that foot problems in patients with rheumatoid arthritis (RA) are highly prevalent, even when classic measures of disease activity suggest clinical remission [20][21][22][23]. Despite great advances in disease management, a large majority of patients remain significantly impaired by foot complications [24].…”
Section: Discussionmentioning
confidence: 99%